Back Cover: An STM Perspective on Hexaborides: Surface States of the Kondo Insulator SmB6 (Adv. Quantum Technol. 12/2021). Issue 12 (9th December 2021) - Wirth, Steffen; Schlottmann, Pedro
Abstract : Experimental efforts are required to confirm the recently proposed topologically non‐trivial nature of the surface states in SmB6 . The cover shows the scanning tunneling microscopy set‐up for the topography and spectroscopy measurements on hexaborides used by Steffen Wirth and Pedro Schlottmann (see article number 2100102 ). Shown is the topography of a SmB6 surface (5.1 nm × 5.5 nm) and a scanning electron microscopy image of a tungsten tip (shaft diameter about 0.3 mm). Tunneling spectroscopy provides local information on the electronic sample properties, in particular the density of states near the sample surface.